Fine structure of the subitaneous eggshell of the sessile rotifer Stephanoceros millsii (Monogononta) with observations on vesicle trafficking in the integument during ontogeny. Issue 2 (3rd April 2019) - Hochberg, Rick; Yang, Hui; Walsh, Elizabeth J.; Wallace, Robert L.
ABSTRACT: Rotifers that engage in cyclical parthenogenesis produce two types of eggs: subitaneous eggs that hatch as clonal females and meiotic eggs that hatch as haploid males, or if fertilized, as females after a period of diapause (resting eggs). The ultrastructure of resting eggshells is known for some motile species, but there are limited data on subitaneous eggshells, and no data on any eggshells of sessile rotifers. Here, we investigated the ultrastructure of the subitaneous eggshell of the sessile rotifer Stephanoceros millsii and its potential origins of secretion, the maternal vitellarium and embryonic integument. We also explored secretory activity in the larval and adult integuments to determine whether activity changes during ontogeny. The eggshell consists of a single layer with two sublayers: an external granular sublayer apparently derived from the maternal vitellarium, and an internal flocculent sublayer secreted by the embryonic integument that may form a hatching membrane or glycocalyx. Secretory activity remains high in both the larva and adult and appears to be the source of the thickening glycocalyx. Altogether, the subitaneous eggshell of S. millsii is the thinnest among monogonont rotifers. Thin eggshells may have evolved in response to the added protection provided by the mother's extracorporeal tube.